Djibouti : Sixth Review Under the Extended Credit Facility Arrangement and Request for Waivers of Nonobservance of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Djibouti. (IMF Staff Country Reports; Country Report, 2013)
The article is a review on Djibouti's Extended Credit Facility (ECF) program and the performance of economic development in the program. The ECF program helped Djibouti to maintain macroeconomic stability, and the period underwent a transformation in the Djiboutian economy. The country saw an economic increase, and the banking system boomed. A positive thought of economic growth is projected in 2012, so plans were targeted to pursue fiscal reforms to improve debt sustainability, strengthening the banking sectors. The authorities of the Executive Board expect another program similar to the ECF.